Experimental investigation of effect of different tube row-numbers, fin pitches and operating conditions on thermal and hydraulic performances of louvered and wavy finned heat exchangers - Okbaz, Abdulkerim; Pinarbasi, Ali; Olcay, Ali Bahadir (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2020)
Heat exchangers are used in air conditioners, heat pumps, marine, land and air vehicles, refrigeration systems, thermal and nuclear power plants, etc. Increasing heat transfer capacity of a heat exchanger means that the volume of the heat exchanger and the material used will be reduced. Besides, effects of some geometric parameters on heat transfer and pressure drop are more complex depending on the fin structure in fin and tube heat exchangers. In this study, three of the most dominant parameters affecting the thermal-hydraulic performance of a finned and tube heat exchanger were experimentally investigated. These are fin-type (louvered and wavy fins), fin pitch and number of tube-rows. The intermittent geometric structures of louvered fins break growing of the boundary layer and reduce its thickness yielding heat transfer enhancement. On the other hand, wavy fins cause an increase in the heat transfer area due to its large flow length and create instabilities in the flow due to flow separations increasing the heat transfer coefficient. In the present study, specifically five louvered firmed and three wavy finned and round tube heat exchanger prototypes were manufactured. Heat transfer and pressure drop experiments of these heat exchangers were performed at a wind tunnel in a conditioned room. Heat transfer and pressure drop characteristics were presented as heat transfer coefficient h(o), Stanton number S-t, Nusselt number Nu, dimensionless pressure drop coefficient C-p, Colbum-j factor, Fanning friction factor f, j(louver)/j(wavy), f(louver)/f(wavy), j/f(1/3) ratios and JF factor. The results were examined from the point of heat transfer and pressure drop mechanisms of louvered and wavy fins for the different number of tube-rows, fin pitches and air inlet velocities. It is found that Colburn-j factors and Fanning friction f factors of the LFRTHXs are higher than those of the WFRTHXs for all the studied cases. Colbum-j factors of the LFRTHXs are higher by 16.4-6.9%, 28.5-18.3% and 25-11.7% than those of the WFRTHXs for the cases of two tube-rows, three tube-rows and four tube-rows, respectively. On the other hand, pressure drops of the LFRTHXs are significantly higher than those of WFRTHXs. However, the thermal-hydraulic performances of the LFRTHXs are still higher than that of WFRTHXs. The thermal-hydraulic performance criteria j/f(1/3) ratios of the LFRTHXs are higher by 9.6-4.1%, 22.1-16% and 16.8-7.4% than those of the WFRTHXs for the cases of two tube-rows, three tube-rows and four tube-rows, respectively.
Keywords: Louvered fins; Wavy fins; Effect of tube row; Fin types; Heat exchanger; Heat transfer; Heat transfer enhancement; Pressure drop; AIR-SIDE PERFORMANCE; FRICTION CHARACTERISTICS; TRANSFER ENHANCEMENT; AIRSIDE PERFORMANCE; FLOW VISUALIZATION; PRESSURE-DROP; FLUID-FLOW; FLAT TUBE; Thermodynamics; Engineering